An interface for running crop models over gridded land surfaces - Sood, R. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The objective of the project is to develop a user interface for running a stripped‐down DSSAT crop models. The work will develop a GUI system that will accomplish three tasks. First, it will provide users a venue to input large volumes of climate scenario, soil and weather data; second, it will optimize the available computer resources to run parallel multiple instances of the DSSAT crop model over very large number of grids for up to global scale1; and third, display the outputs. The graphical user interface will be developed using Visual Basic. This document describes different types of files that are used in the DSSAT model and in the interface. It then describes the process in detail.